2020
DOI: 10.1371/journal.pone.0229129
|View full text |Cite
|
Sign up to set email alerts
|

Selective exposure shapes the Facebook news diet

Abstract: The social brain hypothesis fixes to 150 the number of social relationships we are able to maintain. Similar cognitive constraints emerge in several aspects of our daily life, from our mobility up to the way we communicate, and might even affect the way we consume information online. Indeed, despite the unprecedented amount of information we can access online, our attention span still remains limited. Furthermore, recent studies showed the tendency of users to ignore dissenting information but to interact with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…This shift from the traditional news paradigm profoundly impacts the construction of social perceptions 14 and the framing of narratives; it influences policy-making, political communication, as well as the evolution of public debate 15 , 16 , especially when issues are controversial 17 . Users online tend to acquire information adhering to their worldviews 18 , 19 , to ignore dissenting information 20 , 21 and to form polarized groups around shared narratives 22 , 23 . Furthermore, when polarization is high, misinformation might easily proliferate 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…This shift from the traditional news paradigm profoundly impacts the construction of social perceptions 14 and the framing of narratives; it influences policy-making, political communication, as well as the evolution of public debate 15 , 16 , especially when issues are controversial 17 . Users online tend to acquire information adhering to their worldviews 18 , 19 , to ignore dissenting information 20 , 21 and to form polarized groups around shared narratives 22 , 23 . Furthermore, when polarization is high, misinformation might easily proliferate 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the popular measures for quantifying inequality in a system [ 37 ]. To assess the impact of news recommendation on overall popularity inequality we also track this metric during the simulation.…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be noted that the prevalence of Echo Chamber-like communication structures is subject to controversial debate (for a short overview see Guess et al, 2019): While some studies, such as a recent analysis of 14 million Facebook users' interactions with news sites over the span of six years (Cinelli et al, 2020), present compelling evidence for online users' preference for selective exposure and their segregation in Echo Chambers, others do not. For example, only a minority of Facebook and Twitter users describe their network as mostly comprised of like-minded others (Duggan & Smith, 2016), a self-report that is backed by an analysis of Australian Twitter users' likelihood to be exposed to attitudinally congruent and incongruent contents (Bruns, 2017), and a recent study based on Eurobarometer survey data could not link self-reported network homogeneity and political polarization regarding attitudes towards the European Union (Nguyen & Vu, 2019).…”
Section: Introductionmentioning
confidence: 99%